MAKNA ANTHEM AKU YAKIN DENGAN KAMU DI SETIAP PERTANDINGAN PSIM JOGJAKARTA - Pratama, Aprilla Ifan (Commsphere: Jurnal Mahasiswa Ilmu Komunikasi, 2023)
Anthem is a song of pride for the supporters of a football club they support. We often hear that from the many chants or chants from friends, football supporters often compete for creativity so that their proud team wins. But from the yells they showed, it was just a chant, not an anthem. The meaning of this separate anthem is very important because it can influence the players he supports to increase enthusiasm and have previous expectations such as criticism when a club that is defended or supported by all parties of management, players, coaching staff and supporters can evaluate or learn from defeat can be conveyed precisely. The emergence of this anthem has also become interesting football, especially in the Indonesian League because it is a relatively new foreign culture related to the era of Indonesian football before 2014 or since the suspension of the Indonesian League at that time. Not to be missed, the presence of this anthem changed drastically when Indonesian football used to be known even today for its riots and anarchism, but at least it has reduced the number of riots as PSIM Jogjakarta supporters who are known as Brajamusti flocked to the existing Mandala Krida or Sultan Agung stadium. in the city of Bantul, south of the city of Jogja, to showcase the anthem I'm Sure With You. Apart from providing more support to the players, athem is basically a way to express love for the club. Keywords: Anthem; Chant; Meaning; PSIM; Football Fans Club